THE CONTENT OF PREPARING FUTURE TEACHERS FOR PROFESSIONAL INNOVATIVE ACTIVITY. (Multidisciplinary Journal of Science and Technology, 2024)
Talking about the importance of evaluation and development of educational processes is a very important topic. This is important for the analysis of students' mastering and learning processes, to determine their level of mastering and to make educational processes more effective. In this thesis, a summary of the preparation of future teachers for innovative activities is expressed.